De-radicalization of children and youth by enhancing nationalism and spirituality through national children's learning program - Diaz Syafrie Abdillah; Akbar Reza Muhammad; Athiyatul Ulya; Hafizh Auliyan Sodali; Dian Dakwatul Choiriya; Handayani Handayani; Hafid Algristian (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2018)
The teenagers and children are groups that are vulnerable to radicalism. This de-radicalized program is an innovation in the field of community service called "Learning Children in the Country". This program is useful to prevent radicalism, by increasing nationalism, spirituality and creativity for children and adolescents. This program consists of two major parts, namely brief material delivery and educational games. To assess the success of this community service program, medicine faculty team of UNUSA used a personality measuring instrument, namely the Radical Personality Test (RPT) in the form of pre-test and post-test. Assessment is carried out in a direct and indirect manner. Direct assessment uses a structured interview method, while indirect assessment through observing children's behavior during the learning program. The results of personality assessment show that the post-test value of nationalism and spirituality increases, while the value of the level of radicalism decreases. Emotionally, KANRI children are more stable and better able to complete the assignments. This community service program succeeded in reducing the level of radicalism in KANRI children.